2013
DOI: 10.1515/jpm-2013-0140
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality due to pandemic influenza A H1N1 2009 virus in Colombia

Abstract: Aims: The 2009 H1N1 pandemic illustrated the higher morbidity and mortality from viral infections in peripartum women. We describe clinical features of women who recently died of H1N1 in Colombia. Methods: This is a case series study that was gathered through a retrospective record review of all maternal H1N1 deaths in the country. The national mortality database of confirmed mortality from H1N1 in pregnancy and up to 42 days after delivery was reviewed during the H1N1 season in 2009. Women with H1N1 infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
(2 reference statements)
1
14
0
Order By: Relevance
“…Final 2015 results are thus based on recent historical data and model results. Third, our CODEm models have limited ability to capture non-stochastic rapid increases and decreases that might occur as a result of epidemics such as Ebola virus and H1N1 influenza,70,71 armed conflicts,72 or other events. Fourth, this report has examined nine specific causal categories of maternal death, but this classification system is certainly not exhaustive.…”
Section: Discussionmentioning
confidence: 99%
“…Final 2015 results are thus based on recent historical data and model results. Third, our CODEm models have limited ability to capture non-stochastic rapid increases and decreases that might occur as a result of epidemics such as Ebola virus and H1N1 influenza,70,71 armed conflicts,72 or other events. Fourth, this report has examined nine specific causal categories of maternal death, but this classification system is certainly not exhaustive.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to young males, the increased fatality rate from the 1918 H1N1pdm virus among pregnant women was associated with secondary bacterial infections (Woolston and Conley 1918;Harris 1919) (Table 6.2). During the 2009 H1N1 pandemic, pregnant women were also at greater risk of a severe outcome, with approximately 80 % of maternal deaths occurring during the third trimester of pregnancy (WHO 2009;Jain et al 2009;Vaillant et al 2009;Rojas-Suarez et al 2014). Although the outcome of seasonal influenza virus infection is less severe than the outcome of pandemic influenza viruses, pregnant women have a longer length of hospitalization from infection with seasonal influenza viruses (Cox et al 2006) (Table 6.2).…”
Section: Infectionmentioning
confidence: 99%
“…The report by Rojas-Suarez et al [11] Using Centers for Disease Control and Prevention (CDC) surveillance data through the end of 2009, we described 56 deaths from 2009 H1N1 among pregnant women in the United States and showed that pregnant women had a disproportionately higher risk of mortality than the general population [12].…”
mentioning
confidence: 91%
“…Therefore, vaccination and prompt empiric therapy are particularly critical for pregnant women in preventing and treating infection and for preventing adverse fetal effects. Of note, in the Columbian case series [11], none of the women who died had received influenza vaccination and many did not receive prompt antiviral therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation